Simplifying
x + 6 = 3x + -14
Reorder the terms:
6 + x = 3x + -14
Reorder the terms:
6 + x = -14 + 3x
Solving
6 + x = -14 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
6 + x + -3x = -14 + 3x + -3x
Combine like terms: x + -3x = -2x
6 + -2x = -14 + 3x + -3x
Combine like terms: 3x + -3x = 0
6 + -2x = -14 + 0
6 + -2x = -14
Add '-6' to each side of the equation.
6 + -6 + -2x = -14 + -6
Combine like terms: 6 + -6 = 0
0 + -2x = -14 + -6
-2x = -14 + -6
Combine like terms: -14 + -6 = -20
-2x = -20
Divide each side by '-2'.
x = 10
Simplifying
x = 10
Answer:
6 dollars and 40 cents
Step-by-step explanation:
To get the answer, you would do 32/5 which equals 6.4, which is the same as saying 6 dollars and 40 cents.
Answer:
b=49
Step-by-step explanation:
27+b=76
76-27= 49
b=49
Answer: The answer is A. Hope this helps :)
Step-by-step explanation: